Jami's Rhetoric of Old Age and Aging in Salaman va Absal. Issue 1 (April 2022) - Fayyaz, Parwana
Abstract : Between the years 1480 and 1484 AD, Jami wrote a long and extraordinary narrative poem, the mas navī of Salaman va Absal . At the time of its completion, Jami was about seventy years old. In this article, I discuss the significance of the poet's age at the time he wrote this poem, while also examining the Sufi–Neoplatonic interpretations of old age embedded in the poem itself. I argue that Jami uses old age as a rhetorical device, and aging as an induction into a new mode of thinking. This allows the poet to emancipate himself from the poem's aesthetics and its aesthetic constraints, to focus instead on its metaphysical purpose and potential. In so doing, the poet elevates his poetry to the status of a kind of perfection, which involves transforming the poetic form. Only then does Jami complete his treatise on the unity of oneness (as opposed to duality) from the perspective of an elderly poet. The unusual, passionate love between Salaman and Absal is presented as a Sufi–Neoplatonic interpretation of transcendence and sublimation. Using an interdisciplinary research methodology, this article examines these ideas through a close reading and analysis of the three chapters of the poem in which Jami draws particular attention to images of old age and aging. With this article, I hope to demonstrate the importance of old age studies within Persianate Studies more broadly. This shift in focus prompts a re-evaluation of the late works of classical and medieval Persian poets and their discussions of creativity, imagination, and memory in old age.